Technology-centered academic library partnerships and collaborations - Doherty, Brian, 1962-; IGI eBooks; IGI Global (Hershey, Pennsylvania (701 E. Chocolate Avenue, Hershey, PA 17033, USA) : IGI Global, 2016)
"This book examines cooperation efforts employed by librarians allowing them to provide more services and resources to their patrons, focusing on the utilization of available digital technologies for the improvement of library functions"--Provided by publisher.
Library collaborative networks forging scholarly cyberinfrastructure and radical collaboration / Laurie N. Taylor [and 6 others] -- Collaborations in liberal arts colleges in support of digital humanities / Lisa M. McFall [and 5 others] -- Online video tutorials and interlibrary resource sharing: a model for understanding the role of internet video in library science and education / Arieh Down Ress, Jaclyn A. McLaughlin, Cynthia Bertuca -- Curricular collaborations: using emerging technologies to foster innovative partnerships / Susan M. Ryan, W. Tandy Grubbs -- The LOUIS consortium and catastrophe / Megan Lowe [and 3 others] -- Academic library collaborations to strengthen open government data and expand librarianship / Tara Das -- The Boston Library Consortium and RapidR: partnering to develop an unmediated book sharing module / Alison R. O'Grady -- Collaboration between researchers and academic library: road to research data country-wide consortium and innovation in library services / Liisi Lembinen -- Collaborating off campus: creating communities of practice with new partners / Adam T. Brisk, Kim Pittman, Matt Rosendahl.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed 06/18/2016).
Keywords: Academic libraries -- Effect of technological innovations on; Library cooperation -- Technological innovations; Academic libraries -- Relations with faculty and curriculum; Communication in learning and scholarship -- Technological innovations; Libraries and colleges; Academic libraries -- United States -- Case studies; Collaborative storage; Collection development; Cyberinfrastucture; Digital humanities; Online tutorials; Open access; Open government data; Electronic books